PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA CANVA UNTUK MENINGKATKAN HASIL BELAJAR IPA MURID KELAS IV SEKOLAH DASAR - Supriono, Tri Indah; Meylan Saleh; Rifda Mardian Arif; Abdul Haris Panai; Irvin Novita Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve students’ science learning outcomes on the topic of energy transformation through the implementation of the Problem-Based Learning (PBL) model assisted by Canva media in Grade IV at SDN 2 Kabila. The study was motivated by the low learning outcomes of students, which were caused by limited student participation during the learning process and the suboptimal use of instructional media. This research employed a Classroom Action Research (CAR) design conducted in two cycles. Each cycle consisted of planning, action implementation, observation, evaluation, and reflection stages. The research subjects were 19 fourth-grade students of SDN 2 Kabila. Data were collected through observation, tests, and documentation. The obtained data were analyzed using descriptive quantitative and qualitative techniques. The findings revealed that the implementation of the Problem-Based Learning model assisted by Canva media was effective in improving students’ science learning outcomes. In the first cycle, only 6 out of 19 students achieved the Minimum Learning Mastery Criteria (≥ 75), representing 31.57%, while 13 students or 68.42% had not yet achieved mastery. After improvements were made in the second cycle, students’ learning outcomes increased significantly, with 18 students or 94.73% achieving mastery, while only 1 student or 5.26% had not yet met the criteria. Therefore, it can be concluded that the implementation of the Problem-Based Learning model assisted by Canva media can significantly improve the science learning outcomes of fourth-grade students at SDN 2 Kabila on the topic of energy transformation.